1992
DOI: 10.2307/3350133
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the Elderly: Workplace Programs for Employed Caregivers

Abstract: An aging population and extended longevity are increasing the number of older people needing informal and family support. At the same time, women, the traditional caregivers, have entered the work force in record numbers. Consequently, concerns about how to care for dependent family members have become workplace issues. In response to the needs of employees who care for family members, employers have produced an array of policies, benefits, and programs, including flexible work schedules and information and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…As Barr, Johnson, and Warshaw (1992) noted, much of the evidence of the impact of workplace elder care programs is anecdotal, based on limited survey data on program use or on data gathered internally through program monitoring.…”
Section: Evaluative Research On Workplace Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Barr, Johnson, and Warshaw (1992) noted, much of the evidence of the impact of workplace elder care programs is anecdotal, based on limited survey data on program use or on data gathered internally through program monitoring.…”
Section: Evaluative Research On Workplace Programsmentioning
confidence: 99%
“…Employees' use of workplace programs has been low, between 1% and 4%, according to reports of employers and elder care program vendors and evaluators (Barr et al, 1992). The decisions and factors related to employees' use of a workplace program offered by two employers were examined by Wagner and Hunt (1994).…”
Section: Use Of Workplace Programsmentioning
confidence: 99%
“…Ward-Griffin et al (2007) found that daughters engaged in "putting themselves in their mothers' shoes" (p. 15) and devising ways of protecting themselves from the hurt inflicted by their mothers as a consequence of the disease. Caregiving daughters also experienced considerable challenges in managing labor force participation along with informal elder-care roles (Barr, Johnson, & Warshaw, 1992;Fromme et al, 2005;Stone & Short, 1990).…”
Section: Family Caregiversmentioning
confidence: 99%
“…The competing demands of work and caring for a dependent relative can cause considerable difficulties for many caregivers. 13 A fifth of people who are in this position reported conflicts with their work, in other words, they sometimes have to work fewer hours, rearrange their schedules or take time off without pay. These problems were related to the degree of disability of the person that they had to supervise.…”
Section: Workplace Programmes For Employed Carersmentioning
confidence: 99%